Micron-sized silica mesh for enhancing the performance of quantum dot sensitized solar cells. Issue 8 (15th April 2022) - Sherafati Tabarestani, Z.; Samadpour, M.
Abstract: Three dimensional silica mesh structures are prepared through a new and simple method for enhancing the quantum dot sensitized solar cells performance and stability. Silica patterns are made on the top of the TiO2 photoanodes and a marked improvement in light scattering properties of meshed structures is confirmed by diffuse reflectance spectroscopy measurements. This improvement enhances the current density and consequently the cells 'efficiency. Parameters of electron transport in cells are explored by electrochemical impedance spectroscopy (EIS). According to the EIS results, silica mesh declines the recombination rate in cells in a clear way. Here more than 50% efficiency improvement is obtained in meshed structures in comparison to cells with normal TiO2 photoanode structures. The insulated silica mesh, reduces the electrolyte's deleterious effect on the semiconductor layers and the cells' stability is improved.